Balanced NOₓ⁻ and proton adsorption for efficient electrocatalytic NOₓ⁻ to NH₃ conversion - Hu, Yue (2024)
Electrocatalytic nitrate (NO3-)/nitrite (NO2-) reduction reaction (eNOx-RR) to ammonia under ambient conditions presents a green and promising alternative to the Haber-Bosch process. Practically available NOx- sources, such as wastewater or plasma-enabled nitrogen oxidation reaction (p-NOR), typically have low NOx- concentrations. Hence, electrocatalyst engineering is important for practical eNOx-RR to obtain both high NH3 Faradaic efficiency (FE) and high yield rate. Herein, we designed balanced NOx- and proton adsorption by properly introducing Cu sites into the Fe/Fe2O3 electrocatalyst. During the eNOx-RR process, the H adsorption is balanced, and the good NOx- affinity is maintained. As a consequence, the designed Cu-Fe/Fe2O3 catalyst exhibits promising performance, with an average NH3 FE of ∼98% and an average NH3 yield rate of 15.66 mg h-1 cm-2 under the low NO3- concentration (32.3 mM) of typical industrial wastewater at an applied potential of -0.6 V versus reversible hydrogen electrode (RHE). With low-power direct current p-NOR generated NOx- (23.5 mM) in KOH electrolyte, the Cu-Fe/Fe2O3 catalyst achieves an FE of ∼99% and a yield rate of 15.1 mg h-1 cm-2 for NH3 production at -0.5 V (vs RHE). The performance achieved in this study exceeds industrialization targets for NH3 production by exploiting two available low-concentration NOx- sources.